Mutation in ESBL Plasmid from Escherichia coli O104:H4 Leads Autoagglutination and Enhanced Plasmid Dissemination - Poidevin, Mickaël; Sato, Mari; Altinoglu, Ipek; Delaplace, Manon; Sato, Chikara; Yamaichi, Yoshiharu (Frontiers in Microbiology, 2018)
Conjugative plasmids are one of the main driving force of wide-spreading of multidrug resistance (MDR) bacteria. They are self-transmittable via conjugation as carrying the required set of genes and cis-acting DNA locus for direct cell-to-cell transfer. IncI incompatibility plasmids are nowadays often associated with extended-spectrum beta-lactamases producing Enterobacteria in clinic and environment. pESBL-EA11 was isolated from Escherichia coli O104:H4 outbreak strain in Germany in 2011. During the previous study identifying transfer genes of pESBL-EA11, it was shown that transposon insertion at certain DNA region of the plasmid, referred to as Hft, resulted in great enhancement of transfer ability. This suggested that genetic modifications can enhance dissemination of MDR plasmids. Such ‘superspreader’ mutations have attracted little attention so far despite their high potential to worsen MDR spreading. Present study aimed to gain our understanding on regulatory elements that involved pESBL transfer. While previous studies of IncI plasmids indicated that immediate downstream gene of Hft, traA, is not essential for conjugative transfer, here we showed that overexpression of TraA in host cell elevated transfer rate of pESBL-EA11. Transposon insertion or certain nucleotide substitutions in Hft led strong TraA overexpression which resulted in activation of essential regulator TraB and likely overexpression of conjugative pili. Atmospheric Scanning Electron Microscopy observation suggested that IncI pili are distinct from other types of conjugative pili (such as long filamentous F-type pili) and rather expressed throughout the cell surface. High transfer efficiency in the mutant pESBL-EA11 was involved with hyperpiliation which facilitates cell-to-cell adhesion, including autoagglutination. The capability of plasmids to evolve to highly transmissible mutant is alarming, particularly it might also have adverse effect on host pathogenicity.